Secondary forest regeneration benefits old-growth specialist bats in a fragmented tropical landscape - Rocha, Ricardo (2018)
Tropical forest loss and fragmentation are due to increase in coming decades. Understanding how matrix dynamics, especially secondary forest regrowth, can lessen fragmentation impacts is key to understanding species persistence in modified landscapes. Here, we use a whole-ecosystem fragmentation experiment to investigate how bat assemblages are influenced by the regeneration of the secondary forest matrix. We surveyed bats in continuous forest, forest fragments and secondary forest matrix habitats, ~15 and ~30 years after forest clearance, to investigate temporal changes in the occupancy and abundance of old-growth specialist and habitat generalist species. The regeneration of the second growth matrix had overall positive effects on the occupancy and abundance of specialists across all sampled habitats. Conversely, effects on generalist species were negligible for forest fragments and negative for secondary forest. Our results show that the conservation potential of secondary forests for reverting faunal declines in fragmented tropical landscapes increases with secondary forest age and that old-growth specialists, which are often of most conservation concern, are the greatest beneficiaries of secondary forest maturation. Our findings emphasize that the transposition of patterns of biodiversity persistence in island ecosystems to fragmented terrestrial settings can be hampered by the dynamic nature of human-dominated landscapes.